2013
DOI: 10.1371/journal.pone.0070084
|View full text |Cite|
|
Sign up to set email alerts
|

Early PTSD Symptom Trajectories: Persistence, Recovery, and Response to Treatment: Results from the Jerusalem Trauma Outreach and Prevention Study (J-TOPS)

Abstract: ContextUncovering heterogeneities in the progression of early PTSD symptoms can improve our understanding of the disorder's pathogenesis and prophylaxis.ObjectivesTo describe discrete symptom trajectories and examine their relevance for preventive interventions.DesignLatent Growth Mixture Modeling (LGMM) of data from a randomized controlled study of early treatment. LGMM identifies latent longitudinal trajectories by exploring discrete mixture distributions underlying observable data.SettingHadassah Hospital u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 42 publications
4
95
1
Order By: Relevance
“…J Clin Psychiatry 76:9, September 2015 to survivors of the 9/11 World Trade Center attacks 6 ; Israeli emergency room patients 7 ; and elderly hurricane survivors. 8 What is distinctive about the Australian study 1 is its comprehensive and precise information on posttraumatic trajectories, with respect both to non-PTSD outcomes and, perhaps most interestingly, to the high level of migration across diagnostic classes as assessed at 3, 12, and 72 months.…”
Section: E1154mentioning
confidence: 99%
“…J Clin Psychiatry 76:9, September 2015 to survivors of the 9/11 World Trade Center attacks 6 ; Israeli emergency room patients 7 ; and elderly hurricane survivors. 8 What is distinctive about the Australian study 1 is its comprehensive and precise information on posttraumatic trajectories, with respect both to non-PTSD outcomes and, perhaps most interestingly, to the high level of migration across diagnostic classes as assessed at 3, 12, and 72 months.…”
Section: E1154mentioning
confidence: 99%
“…Early interventions may reduce the prevalence of chronic PTSD among survivors at risk (Kearns, Ressler, Zatzick, & Rothbaum, 2012), but they are resource demanding and effective in only a subset of survivors. The frequent presence of spontaneously remitting early symptoms (Bryant et al, 2015; Galatzer-Levy et al, 2013) makes it difficult to differentiate those at risk for chronic disorder from those who will remit on their own. This, in turn, constitutes a barrier to targeting prevention efforts to those at risk.…”
Section: Introductionmentioning
confidence: 99%
“…The course of PTSD is variable, with some studies finding a favourable outcome and low rates of chronicity [7]; however, long-term studies have found that at least half the patients initially diagnosed with PTSD continue to experience symptoms after several years [6,8,9]. Chronic PTSD is associated with marked impairments in social and occupational functioning and is often associated with other mental disorders such as depression, anxiety disorders, and substance use disorders [10].…”
Section: Introductionmentioning
confidence: 99%